David Sassoon Clocktower - Ghosh, Ayan (2023)
The David Sassoon Clock Tower originally stood outside the gates of Victoria Garden, by the side of the main road, then known as Parel Road (now BR Ambedkar Road). In 1926, during the widening of the road, the clock tower was dismantled brick by brick and reconstructed at its present location. During shifting, the earlier alignment was retained, and the successful relocation of the structure set a good example of sensitive heritage conservation.